Asthma in Sickle Cell Disease: Implications for Treatment - Blake, Kathryn (Hindawi Publishing Corporation, 2011)
Objective. To review issues related to asthma in sickle cell disease and management strategies. Data Source. A systematic review of pertinent original research publications, reviews, and editorials was undertaken using MEDLlNE, the Cochrane Library databases, and CINAHL from 1947 to November 2010. Search terms were [asthma] and [sickle cell disease]. Additional publications considered relevant to the sickle cell disease population of patients were identified; search terms included [sickle cell disease] combined with [acetaminophen], [pain medications], [vitamin D], [beta agonists], [exhaled nitric oxide], and [corticosteroids]. Results. The reported prevalence of asthma in children with sickle cell disease varies from 2% to approximately 50%. Having asthma increases the risk for developing acute chest syndrome , death, or painful episodes compared to having sickle cell disease without asthma. Asthma and sickle cell may be linked by impaired nitric oxide regulation, excessive production of leukotrienes, insufficient levels of Vitamin D, and exposure to acetaminophen in early life. Treatment of sickle cell patients includes using commonly prescribed asthma medications; specific considerations are suggested to ensure safety in the sickle cell population. Conclusion. Prospective controlled trials of drug treatment for asthma in patients who have both sickle cell disease and asthma are urgently needed.